2016
DOI: 10.1089/ten.tec.2015.0581
|View full text |Cite
|
Sign up to set email alerts
|

Surface Chemistry and Microtopography of Parylene C Films Control the Morphology and Microtubule Density of Cardiac Myocytes

Abstract: Cell micropatterning has certainly proved to improve the morphological and physiological properties of cardiomyocytes in vitro; however, there is little knowledge on the single cell-scaffold interactions that influence the cells' development and differentiation in culture. In this study, we employ hydrophobic/hydrophilic micropatterned Parylene C thin films (2-10 mm) as cell microscaffolds that can control the morphology and microtubule density of neonatal rat ventricular myocytes (NRVM) by regulating their ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 33 publications
1
13
0
Order By: Relevance
“…The PP1 scaffolds, after three days from a mild treatment (RIE), show a contact angle almost constant with a value of 80°, still good for cell adhesion. The substrates with a contact angle of 80° are considered weakly hydrophobic [56] and this value of contact angle can be still considered good for promoting cell adhesion as reported by Trantidou et al in [51].…”
Section: Accepted Manuscriptmentioning
confidence: 96%
See 2 more Smart Citations
“…The PP1 scaffolds, after three days from a mild treatment (RIE), show a contact angle almost constant with a value of 80°, still good for cell adhesion. The substrates with a contact angle of 80° are considered weakly hydrophobic [56] and this value of contact angle can be still considered good for promoting cell adhesion as reported by Trantidou et al in [51].…”
Section: Accepted Manuscriptmentioning
confidence: 96%
“…The contact angle of PDMS1 employed on PP2 scaffolds after three days from a strong plasma treatment (ICP) remains almost constant with a value below 60° that was demonstrated to be good for cell adhesion [51], [52]. This result is advantageous for promoting cell adhesion.…”
Section: Surface Wettabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Micro and nanofabrication methods allowed to transfer the information at these scales in a controlled, predefined, and versatile way ( Figure 2 a) [ 26 ]. Optical lithography was used to direct the attachment of cardiac cells cultured on surfaces, having a patterning with 20-μm wide lines, to control the morphology and microtubule density of cardiac myocytes [ 27 ]. Methacrylated tropoelastin (MeTro) coating by means microfluidic method allowed the neonatal rat CMs attachment and beating [ 28 ].…”
Section: Nanopatterning Technologies For Cardiac Tissue Regeneratimentioning
confidence: 99%
“…Optical lithography is also used to direct the attachment and the shape of cells which are grown on surfaces. It has been found that when cardiac cells are cultured on surfaces that have been patterned into having typically 20 m wide lines, cells tend to align and stretch their ECM and their nucleus towards the length of the line [27]. Aligning CMs is crucial for the contraction and propagation along the long axis [28].…”
Section: Optical Lithographymentioning
confidence: 99%